2008
DOI: 10.3130/jaabe.7.293
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Environmental Quality in LEED-Certified Buildings in the U.S.

Abstract: The purpose of this study was to evaluate the indoor environmental quality (IEQ) of workplaces in the LEED-certified buildings in the United States. LEED ® , standing for the Leadership in Energy and Environmental Design, is a U.S. national sustainable building benchmark as well as green building rating system adopted nationally and internationally. The study compared seven IEQ criteria in relation to occupant's satisfaction and performance between LEED-certified buildings and non-LEED-certified buildings. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 3 publications
5
55
2
1
Order By: Relevance
“…The findings of our study in terms of mean values of occupant satisfaction with indoor environmental quality in commercial office buildings -both LEED and non-LEED rated -are also broadly consistent with those of other earlier studies on the CBE database (e.g., [1,21,22,36,37]), that reported low satisfaction particularly with their thermal and acoustic environment. As previously mentioned -in both LEED and non-LEED certified buildings -the lowest mean score of satisfaction was observed with sound privacy (LEED: M= -0.96; non-LEED: M= -0.88).…”
Section: Occupant Satisfaction With Ieq In Office Buildingssupporting
confidence: 80%
See 4 more Smart Citations
“…The findings of our study in terms of mean values of occupant satisfaction with indoor environmental quality in commercial office buildings -both LEED and non-LEED rated -are also broadly consistent with those of other earlier studies on the CBE database (e.g., [1,21,22,36,37]), that reported low satisfaction particularly with their thermal and acoustic environment. As previously mentioned -in both LEED and non-LEED certified buildings -the lowest mean score of satisfaction was observed with sound privacy (LEED: M= -0.96; non-LEED: M= -0.88).…”
Section: Occupant Satisfaction With Ieq In Office Buildingssupporting
confidence: 80%
“…The conclusions of our study in terms of comparison between occupant satisfaction in LEED and non-LEED certified buildings are considerably different from previous analysis of data extrapolated from the CBE survey database [16][17][18][19][20][21][22]. In fact, earlier studies had concluded that LEED rated/green buildings were generally characterized by higher occupant satisfaction with the building, the workspace, air quality, cleaning and maintenance, and thermal comfort.…”
Section: Leed Vs Non-leedcontrasting
confidence: 55%
See 3 more Smart Citations